Uma proposta de ensino semipresencial de programação apoiada por Juiz On-line e Ambiente Virtual de Aprendizagem Móvel - Oliveira, André Santos (2017)
Computer programming is an integral curriculum’s part of various courses in computing and engineering. However, learning how to code is a complex task because of several problems faced by students and teachers during this process. The evolution in the field of Information and Communication Technology is allowing to change the process of teaching and learning in order to meet the new demands of education. The use of virtual learning environments and other tools, such as online judges systems, emerge as a proposal to meet the new educational needs in teaching and programming learning scenario. In addition, in recent years, advances in mobile computing area allow for an alternative to enlarge the process of teaching and learning in education. In this context, this paper presents a proposal for a semipresential methodology for programming teaching supported by online judge, and mobile and Web virtual learning environment. These computational tools were described with their main functionalities adapted and used to the proposed methodology. The proposal was evaluated through a case study in classes of the discipline Introduction to Computer Science (ICC), from the Computer Department from the Federal University of Sergipe (DComp/UFS), that focus on computer programming. First, the study analyzed the academic performance of the classes of the DComp/UFS ICC discipline that used the traditional approach, from 2002 to 2016, from REUNI’s point of view, which showed better performance when compared with the classes before REUNI. In relation to the groups that used the proposed methodology, from 2015 to 2016, the results were compared with those of the past classes after REUNI taught only by e ective teachers. It was identified that the classes that used the proposed methodology, except those of 2016 after repositive test, that obtained better results, had a slightly lower percentage of approvals when were compared with those classes after REUNI taught only by e ective teachers. However, those classes that used the proposed methodology had better results with respect to the percentages of disapproval. It was evaluated that the compliance of the Study Guide activities and the use of the online judge The Huxley by the students for the practical activities of programming influence the approval of the student. In addition, research was carried out with the students that allowed to identify the experience in the use of proposed methodology and its support tools brought benefits to their learning, but there are still some proposed improvements to apply in the methodology. As a contribution, it is hoped that this proposed methodology and the tools that support it can be used in other classes, in other disciplines and in other institutions, thus improving computer programming learning, that is one of the knowledge bases of Software Engineering and Computing.